Patient Repositioning during Hospitalization and Prevention of Pressure Ulcers: a Narrative Review - L. Cortés, Olga; M. Vásquez, Skarlet (Investigación y Educación en Enfermería, 2024)
Objective. This article presents a literature review to explore and analyze the current situation of pressure ulcers or lesions or decubitus ulcers, pathophysiological, epidemiological aspects, and risk factors. The progress in evidence of the effectiveness of preventive repositioning in the appearance of these lesions in vulnerable hospitalized patients is also evaluated. Methods. Databases were reviewed in non-systematic manner, including the Cochrane Wounds Specialized Register; Medline, Scopus, PubMed, the Cochrane Central Register of Controlled Trials; MEDLINE (Ovid); EMBASE (Ovid), Web of Science, SciELO, and Lilacs. The general search terms included [pressure ulcers or pressure lesions or decubitus ulcers] and [prevention or preventive] and [repositioning or positioning or position changes or postural change] and [patient at risk or vulnerable] and [hospitalized or ICU or intensive care]. Systematic literature reviews, randomized clinical trials, observational studies, cost-effectiveness and qualitative studies in English or Spanish were included. Results. Although globally, the incidence, prevalence, and years of disability associated to these lesions has diminished between 1990 and 2019, the high impact on health persists. Evidence found on the effectiveness of repositioning in preventing pressure ulcers and health associated costs has been evaluated with certainty between low and very low, as a result of conducting research with serious methodological limitations that report results with high inaccuracy. Conclusion. The findings reported present that these lesions persist at hospital level and continue being a global social and health problem with high impact on health budgets. Likewise, there is a need to develop greater quality research on prevention strategies, such as repositioning, which validate their effectiveness, and justify their use.